A importância da Lei Nº 8137/90 e os instrumentos utilizados pela SEFAZ no combate à sonegação fiscal no Ceará - Camurça, Glauber Capistrano (2011)
The taxes grew in importance as the State received greater demands, and it was necessary a more active supervision, more committed to the exchequer. The administrative machinery has come to view the activity of the tax police as something essential, without which it could survive. Trying to reduce the tax evasion, the State of Ceará has implemented operating systems that inhibit and tried to reach the evaders. Oversight of operations Tax VAT on Goods and Services Rendered on Interstate Transportation and Communication has the means, and ways to combat crimes against the tax. And using a blow, inspecting, investigating, monitoring, observing and monitoring those who try to cheat the taxman. Law n. 8137/90 came as support to inhibit many of the tax fraudsters. It is an important part to be analyzed, defining the crimes that typify who works contrary to the laws of the ICMS. And at another way, the ways that the SEFAZ uses to elucidate so many irregularities in optimizing revenue and making the tax an instrument to create a more just and democratic society where everyone can enjoy the social and economic function of the tax.